Pengaruh Pemberian Takaran Abu Sekam Padi pada Tanah Gambut terhadap Pertumbuhan dan Hasil Pakcoy - Nur Handayani; Joko Purnomo; Yudhi Ahmad Nazari (Universitas Lambung Mangkurat, 2020)
This research aimed to determine the effect and best dosage of rice hull ash on peat soils to growth and yieId of pakcoy. The research was conducted in September 2019 – November 2019 at the ExperimentaI Garden, AgricuIture FacuIty of Lambung Mangkurat University, Banjarbaru. This research used a CompIeteIy Randоmized Design (CRD), single factor. The treatment factors were dosage of the rice hull ash (A) with seven types of treatment, namely a0=0,a1=2,a2=4,a3=6,a4=8,a5=10,a6=12 (tons ha-1). Each treatment was repeated four times so that there were 28 units of trial. Parameters is observed the number of leaves, plant height, root canopy ratio, total fresh weight of plant, fresh weight of sale, and yield of pakcoy. The resuIts showed that the treatment of rice hull ash not significant affect the pIant height, number of Ieaves, root canopy ratio, totaI fresh weight of pIant, fresh weight of sale, root canopy ratio and yield of pakcoy